Lakatos’s Methodology and its Application to Logic Research Programs: A Comparative Study - Molick, Sanderson (Logic and Logical Philosophy, 2026)
Lakatos’s (1978) methodology of research programs is renowned for describing the evolution of scientific theories through a combination of heuristic mechanisms that guide their development. Various attempts to apply Lakatos’s framework to research programs in logic and mathematics are found in (Priest, 1989; Aberdein and Read, 2009; Hallett, 1979a). The paper draws on Lakatosian assessments of progressive and degenerating mathematical theories found in (Hallett, 1979a) to advance a heuristic proposal for studying the progress and development of logical theories. The upshot is a characterization of Lakatos’s framework as applied to logical theories, along with a defense of a holistic approach that acknowledges the iterative relationship between empirical input and logical refinement during the process of development of progressive logical theories.